Pertumbuhan, Produktivitas, dan Rendemen Pertanaman Tebu Pertama (Plant Cane) Pada Berbagai Paket Pemupukan - Nunik Eka Diana; . Supriyadi; . Djumali (Jurnal Ilmu Pertanian Indonesia, 2016)
Fertilization is an effort improving soil fertility to obtain optimal results. fertilization with the right amount and type can increase growth, productivity, and yield. The study aims to understand the response of growth, productivity, and yield of sugarcane crop (plant cane) against various packages fertilization. The activities carried out in KP. Asembagus, Situbondo began November 2012-October 2013. Seven package dose of fertilizer, namely: 1) 600 kg of new inorganic compound fertilizer + 100 kg ZA; 2) 900 kg of new inorganic compound fertilizer 900 kg + 150 kg ZA; 3) 1.200 kg of new inorganic compound fertilizer + 150 kg ZA; 4) 900 kg of new inorganic compound fertilizer + 3 tons of organic fertilizer A; 5) 900 kg of new inorganic compound fertilizer + 3 tons of organic fertilizer B; 6) 600 kg of old inorganic compound fertilizer type I + 300 kg ZA; 7) 600 kg old inorganic compound fertilizer type II + 500 kg ZA arranged in a randomized block design was repeated three times. The results showed that the fertilizer package 2, 3, and 7 generates growth and productivity tends to be higher, while the fertilizer package (except packet 5) produces yields tend to be higher. The fertilizer package 1, 2, and 3 resulted in the production of crystal tends to be higher.